2019
DOI: 10.1101/610089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bottom trawl catch comparison in the Mediterranean Sea: Flexible Turtle Excluder Device (TED)vstraditional gear

Abstract: 16The Mediterranean Sea is a hotspot of biodiversity, but the high fishing pressure results in high 17 bycatch rates of protected (sea turtles and cetaceans) and top predator species (sharks). The 18 reduction of bycatch is challenging for fishery scientists, as conservation of these species has 19 become a priority. Among the animals threatened by fishing activities, the loggerhead (Caretta 20 caretta) represents a charismatic species considered as "vulnerable" at the global scale by IUCN. 21 In the Medite… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Selection grids aimed at reducing bycatch of undersized individuals have been tested in some areas of the Mediterranean (Sardà et al, 2005;Massuti et al, 2009;Özvarol, 2016). Although this device was proposed in the early 1980s to reduce the capture of large sized animals, such as sea turtles (Epperly, 2003;Lucchetti et al, 2016;Lucchetti et al, 2019;Vasapollo et al, 2019), experiments have shown that grids can be used to reduce the catch of juveniles, without affecting the catch of large sized fish Aydın and Tosunoglu, 2011). Therefore, according to the characteristics of the fishery and the target species, different typologies of grids can be used.…”
Section: Discussionmentioning
confidence: 99%
“…Selection grids aimed at reducing bycatch of undersized individuals have been tested in some areas of the Mediterranean (Sardà et al, 2005;Massuti et al, 2009;Özvarol, 2016). Although this device was proposed in the early 1980s to reduce the capture of large sized animals, such as sea turtles (Epperly, 2003;Lucchetti et al, 2016;Lucchetti et al, 2019;Vasapollo et al, 2019), experiments have shown that grids can be used to reduce the catch of juveniles, without affecting the catch of large sized fish Aydın and Tosunoglu, 2011). Therefore, according to the characteristics of the fishery and the target species, different typologies of grids can be used.…”
Section: Discussionmentioning
confidence: 99%